The durability of basalt-fiber-reinforced cement mortar under exposure to unilateral salt freezing cycles - Zhou, Jiguo; Wang, Guihua; Zhu, Guangxing (Frontiers in Materials, 2023)
Basalt fiber cement-based materials have been widely applied in engineering structures. In this context, the durability of the basalt fiber-reinforced ordinary silicate mortar was systematically studied under unilateral salt freezing in this work. The mechanical durability, chloride ion diffusion, and microscopic pore characteristics of the cement mortar with a basalt fiber content of 0 kg/m3-1.5 kg/m3 were tested under the implementation of freeze-thaw cycles for 0-40 times. The relationship of the internal pore change with the mass loss, mechanical damage, and physical properties was also analyzed under the application of salt freezing cycles. Based on the acquired results, it was demonstrated that even a small amount of basalt fiber can significantly improve the mechanical properties and resistance to salt freezing erosion for cement mortar under unilateral salt freezing. Particularly, the cement mortar with a basalt fiber content of 1.2 kg/m3 exhibited good durability of compressive and flexural strength, while the specimens without basalt fiber had a relatively large internal porosity under the application of unilateral salt freezing. Our work provides concrete pieces of evidence for the change of porosity in the mortar that has an exponential correlation with the mass loss of the mortar, and has a strong linear correlation with the change of the compressive strength, flexural strength, and chloride ions diffusion coefficients under the application of unilateral salt freezing.